Plastics in the cold marine environment: a review of the potential for microbial biodegradation (Research, Society and Development, 2021)
Plastics are widely used products due to their desirable properties for several industrial sectors, such as durability, plasticity, and transparency. Tons of this material has been accumulating in different environments around the world, making it an environmental problem. An alternative to eliminating this material is the search for microorganisms adapted to the cold, which develop different catalytic pathways to adapt to low temperatures, being able to synthesize enzymes capable of metabolizing these materials. Due to the absence or low activity of these enzymes, this strategy is still a challenge with no effective solution. The purpose of this review was to evaluate research on the biodegradation of plastics by microorganisms from cold marine environments, in the last 10 years, using the following descriptors: “Plastic biodegradation AND cold oceans”, “Plastic biodegradation AND (Psychrophile OR Psychrophilic)”, “PETases AND (bacteria OR fungus)” and “Extremophile AND plastic biodegradation”. A survey of publications was carried out on the scientific bases Pubmed, Scopus, and on the Google Scholar search tool. About 11.481 works were found, of which 97.9%, 1.84%, and 0.26% were retrieved from Google Scholar, Scopus, and Pubmed, respectively. Species belonging to the genera Streptomyces, Corynebacterium, Arthrobacter, Micrococcus, Pseudomonas, and Rhodococcus were the most frequently mentioned as potential degraders of plastics in cold marine environments. The results of this work show that studies focused on the degradation of plastics by microorganisms in a cold environment are still scarce, thus opening perspectives for new studies to be carried out addressing this theme.